Superior oxidation resistant MCrAlY bond coats prepared by controlled atmosphere heat treatment. (1st July 2020) - Meng, Guo-Hui; Liu, Hong; Xu, Peng-Yun; Li, Guang-Rong; Xu, Tong; Yang, Guan-Jun; Li, Chang-Jiu
Graphical abstract: Highlights: A novel controlled atmosphere heat treatment (CAHT) was developed in this study. The oxidation resistance of heat-treated bond coats was improved. Large grain α-Al2O3 was formed on the surface of bond coats during CAHT. Large grain α-Al2O3 significantly improved the oxidation resistance of bond coats. The α-Al2O3 grain size can be controlled by the oxygen partial pressure of CAHT. Abstract: Long-life thermal barrier coatings for high-performance gas turbines require MCrAlY bond coats with high oxidation resistance. In this study, the oxidation resistance of bond coats was significantly improved by a novel controlled atmosphere heat treatment (CAHT). Results show that large α-Al2 O3 grains with a grain size up to micron were formed on the surface of heat-treated MCrAlY bond coats. These large α-Al2 O3 grains significantly improved the oxidation resistance of bond coats. We found that the grain size of α-Al2 O3 and the surface microstructure changes of bond coats can be controlled by the oxygen partial pressure of CAHT.